Exponential synchronization of dynamical complex networks via random impulsive scheme - Zhou, Bowen; Shu, Xiao-Bao; Xu, Fei; Yang, Fengyu; Wang, Ya (Nonlinear Analysis: Modelling and Control, 2024)
This paper investigates the synchronization of a complex network based on a class of random impulsive differential equation systems. Based on the random impulsive strategy of Poisson distribution, a random impulsive dynamical network model is constructed. Using the Lyapunov principle, random process theory, linear matrix inequality method, and some basic analysis methods, we realize the global mean-square index synchronization of the model. We then get sufficient criteria for the synchronization. By presenting a numerical example, we verified the validity of the theoretical results.
Keywords: random impulse; synchronization control; dynamic network